PENGARUH IKLAN, KEPERCAYAAN MEREK DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN INDIHOME DI GIANYAR - Kokmang Ayu Noviningsih; Ni Putu Nita Anggraini; Pande Ketut Ribek (VALUES, 2022)
In the current era of globalization, telecommunications plays a very important and strategic role in social life. Through communication technology, the community can exchange information remotely in a relatively fast and efficient time. The purpose of this study was to determine and explain the effect of brand trust and brand image on the buying interest of IndiHome consumers in Gianyar. The population in this study are consumers17,250 units using IndiHome in Gianyar in 2020. The number of samples used in this study were 100 respondents using the purposive sampling method, data collection using a Likert scale questionnaire. The data analysis technique used multiple linear regression test. Hypothesis testing was carried out using the t test. The results showed that there was a positive and significant effect of brand trust and brand image on the buying interest of IndiHome consumers in Gianyar.